PARTISIPASI PEDAGANG DALAM REVITALISASI PASAR TRADISIONAL STUDI KASUS: PASAR KARANGAYU KOTA SEMARANG - Arnelly Rosiana; Priyatno Harsasto; Suwanto Adhi (Journal of Politic and Government Studies, 2017)
AbstrackOne of the government's efforts in maintaining the existence of traditional markets is the establishment of the Minister of Home Affairs Regulation No. 20 of 2012 on Management and Empowerment of Traditional Markets. This research will reveal the participation of traders in the process of revitalizing traditional markets conducted by the government as a form of implementation of efforts to preserve traditional markets.This study aims to analyze the extent to which the participation of traders in planning and implementation of market revitalization Karangayu conducted by the Market Office of Semarang City. In this study researchers used qualitative research methods descriptive approach, namely research that describes a symptom that has occurred and analyze these symptoms through qualitative research procedures.The results of this study indicate that every process of participation provided by communities and traders is important because participation influences the success or failure of traditional market revitalization programs. The form and pattern of cooperation realized between the Market Office, Market Managers and Traders implemented is evidence that the traditional market revitalization process has not been going well enough without the definite support of the community even though the traders are very active in participating. Government must always involve community participation in every stage of revitalization of traditional market in Semarang City not only at certain stage only because people who better understand what they want related to policy implemented.(Keywords: traditional market revitalization, traders' participation, traditional market existence).